Endothelial Dysfunction, a Marker of Atherosclerosis, Is Independent of Metabolic Syndrome in NAFLD Patients. (17th July 2020) - Narayan, Jimmy; Das, Haribhakti Seba; Nath, Preetam; Singh, Ayaskanta; Mishra, Debakanta; Padhi, Pradeep Kumar; Singh, Shivaram Prasad
Abstract : Background . The study was designed to assess cardiovascular risk factors flow-mediated dilatation % (FMD%) and carotid intima-media thickness (CIMT) in NAFLD. Methods . 126 NAFLD subjects and 31 chronic hepatitis B (CHB) controls were studied. Measuring carotid intima-media thickness (CIMT) and the flow-mediated dilatation % (FMD%) by brachial artery Doppler ultrasound were used to assess atherosclerosis. The risk of cardiac events at 10 years (ROCE 10) was estimated by the Prospective Cardiovascular Munster Study (PROCAM) score. Results . 58 of 126 NAFLD have coexistent metabolic syndrome. Mean CIMT was 0.73 ± 0.041   mm among NAFLD with MS, 0.66 ± 0.016   mm among NAFLD without MS, and 0.66 ± 0.037 in controls CHB patients. FMD% in NAFLD with MS was 10.43 ± 3.134 %, but was 8.56 ± 3.581 % in NAFLD without MS and 17.78 ± 6.051 % in controls. PROCAM score of NAFLD with MS was 46.95 ± 6.509 while in NAFLD without MS was 38.2 ± 3.738 . Controls had a PROCAM score of 38.13 ± 5.755 . ROCE 10 in NAFLD with MS was 13.64 ± 8.568 while NAFLD without MS was 5.55 ± 1.949 . Controls have a ROCE 10 of 5.95 ± 3.973 . Post hoc analysis showed CIMT was dependent upon MS while FMD% was different between all subgroups hence independent of metabolic syndrome. Conclusion . The markers of endothelial dysfunction are significantly higher in patients with NAFLD than controls.